Karakteristik Minuman Fungsional Kaya Antioksidan dari Buah Tomi-Tomi (Flacourtia inermis) dengan Penambahan Ekstrak Jahe Merah (Zingiber officinale var. rubrum) dan Fuli Pala (Myristica fragrans Houtt) - Nurjanna Albaar; Hamidin Rasulu; Abdul Syukur Lumbessy; Mila Fatmawati (Jurnal Pertanian Khairun, 2026)
This study aims to evaluate the physical, chemical, and organoleptic characteristics of a functional beverage based on tomi-tomi fruit (Flacourtia inermis) with the addition of extracts of red ginger (Zingiber officinale var. rubrum) and nutmeg mace (Myristica fragrans). Tomi-tomi are known to be rich in vitamin C and phenolic compounds, while red ginger and nutmeg mace contribute to antioxidant activity as well as other functional properties. The study used a complete random design (RAL) with variations in the concentrations of red ginger extract (1%, 2%, 3%) and nutmeg mace (0.25%, 0.5%, 0.75%). The parameters analyzed included total phenolics, antioxidant activity (DPPH), pH, total dissolved solids (TPT), as well as organoleptic tests (color, aroma, taste, and overall acceptance). The results showed that the addition of red ginger extract and nutmeg mace significantly increased the antioxidant activity of the drink. The best treatment was obtained in a combination of 2% red ginger extract and 0.5% nutmeg mace with a total phenolic 235.6 mg GAE/100 mL, antioxidant activity of 82.4%, pH 3.75, TPT 12.1 °Brix, and a high rate of panelist acceptance. The conclusion of this study is that the combination of tomi-tomi fruit, red ginger, and nutmeg mace has the potential to be an antioxidant-rich functional drink with sensory characteristics that consumers prefer.